Pendampingan Pelatihan Pembuatan Buket untuk Meningkatkan Kreativitas dan Pendapatan Masyarakat Dukuh Tengah Desa Nambangrejo Kecamatan Sukorejo Kabupaten Ponorogo - Hidayati, Fiki Nurul; Ansori, Teguh (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research is motivated by the potential of human resources that have not been fully explored. The majority of the population in Dukuh Tengah, Nambangrejo Village—particularly housewives and the younger generation—have free time that could be optimized for productive activities. This is due to limited access to skills training and a lack of exposure to creative economic opportunities. This assistance aims to enhance the community's creativity and skills, increase their knowledge about digital marketing and the use of information technology, boost income, and create new job opportunities for the Dukuh Tengah community. The method used is Asset-Based Community Development (ABCD). This program can empower the Dukuh Tengah community through bouquet-making and digital marketing training, targeting mothers and young women in Dukuh Tengah. The results of the study showed a significant increase in participants' skills in flower arranging after the training, as well as an improvement in their knowledge of digital marketing based on the materials provided.